PEMBELAJARANCOLLABORATIVE WRITINGDALAM PENINGKATAN MUTU PROPOSAL PENELITIAN MAHASISWA - Widhiyant, Widhiyant (Jurnal Penelitian Pendidikan, 2011)
This article is based on classroom action research done in the context of Systemic Functional Linguistics. The contextual teaching and learning activities are applied in helping students develop their research proposal through rhetorical development systems, and employ the systems which are realized in the clauses for their moves and steps. It is done in a class of Academic writing in English Department of UNNES. The main goal of this study is to help students improve the way how to communicate their meanings through texts they develop. The problems are: (1) How can teachers apply collaborative writing technique in Academic Writing class? And (2) How does collaborative writing technique help students cope with problems in developing their research proposal for their thesis? There is a positive impact on the use of collaborative writing technique on the teaching and learning process of Academic Writing class in writing research proposal, as shown in the result of the evaluation of the process and of the composition done by students during the research.It makes students to be active, to work with a good spirit and enjoy the process in the classroom. It can be seen from the result of the evaluation of the observation.